PENGARUH GOOD CORPORATE GOVERNANCE, KINERJA LINGKUNGAN DAN PERTUMBUHAN PENJUALAN - Muhdin Muhdin; Sulaiman Sarmo; Iwan Kusuma Negara (Universitas Muhammadiyah Jember, 2022)
This study aims to examine the effect of Good Corporate Governance (GCG), environmental performance and sales growth on return on assets (a case study on manufacturing companies on the IDX in 2017-2019). This type of research is associative which aims to determine the relationship between two or more variables. The type of data used in this research is quantitative data. The research population is a manufacturing company listed on the Indonesia Stock Exchange and the sampling technique used is purposive sampling with a sample size of 57. Data processing uses multiple regression with the SPSS program. The results showed that GCG, environmental performance, sales growth simultaneously affect the return on assets. While partially the size of the board of directors and institutional ownership and sales growth variables have no effect on return on assets. The audit committee variable and environmental performance have an effect on return on assets, this implies that manufacturing companies in this global era, if oriented towards the environment, will increase profitability. In addition, the role of the audit committee is very important in managing the company to increase profitability.